Maternal Obesity as a Risk Factor for Caesarean Section Delivery: A Case-control Study - Khadka Chhetri, Merina; Dewan, Pramila; Shrestha, Sharmila (Journal of Karnali Academy of Health Sciences, 2021)
Background: The rate of obesity is rising in Nepal and it has increased rapidly among women of reproductive age group over the last decade. Similarly, the rate of caesarean section has also shown an increasing trend in the country over the same period. The objective of this study was to identify maternal obesity as a risk factor for caesarean section in Kathmandu valley.Methods: An analytical case-control design was used to conduct the study. A total of 300 participants, 150 caesarean section deliveries as cases and 150 vaginal deliveries as age-matched controls were selected using purposive sampling technique. Data were collected through interview schedule using a semi-structured questionnaire and medical records review in Paropakar Maternity and Women's Hospital postnatal ward. The Pearson's chi-square test and odds ratio were used to test the association.Results: The study findings revealed a mean body mass index of 24.32±3.96 among the caesarean section delivery group and 21.94±3.34 among the vaginal delivery group (P< 0.001). Obesity was found in 44.67% of the caesarean section delivery group and 18.67% in the vaginal delivery group. There was a significant association between maternal obesity and caesarean section delivery with adjusted OR 4.14, 95% CI: 2.34- 7.20 (P